Inertial sensor, 3D and 2D assessment of stroke phases in freestyle swimming - Lee, J. B.; Burkett, B. J.; Thiel, D. V.; James, D. A. (Procedia Engineering, 2011)
Assessment of human movement kinetics and kinematics use various methods of capture. Typical systems used are 2D or 3D camera systems. These laboratory-based simulations have accurately estimated movement variables. While these systems have shown accuracy in assessment, there are inherent problems with capture capabilities including: simulation of actions, and limitation of the camera system's capture range. Therefore data capture in a realistic environment is usually quite inhibitory. Microtechnology has been shown to address these restrictive issues of assessing human movement. The use of inertial sensors for land and water based biomechanical applications has been steadily gaining popularity. Traditional systems are severely hampered in aquatic environments, due to problems imposed by liquids that are not present in gaseous surroundings. These limitations do not intrude on inertial sensor captured data. Prior to a water based research, inertial sensor technology would require validation. The aim of this study was to validate an inertial system to measure temporal kinematics of a freestyle armstroke on a swimming bench. Six participants simulated freestyle swimming action. Variables measured were components of the stroke phase. A triaxial inertial sensor was positioned on the dorsal side and at the distal end of the forearm. Validation was carried out with comparisons against 2D video capture and a 3D infrared camera system. For statistical analysis, a Pearson's correlation, typical error of estimate, and mean bias were applied. Very large correlations, along with minimal error and mean bias indicate that inertial sensors as a viable option for swimming armstroke assessment.